Digital Leadership in Realizing Bureaucratic Reform in the South Sulawesi Provincial Government - Rahman, Jufri; Ilham, Muh; Rowa, Hyronimus; Thahir, Baharuddin; Rahmadany, Andi Fitri (Journal of Humanities and Social Sciences Studies, 2024)
Bureaucratic reform efforts over the years have yet to yield optimal results, leaving government bureaucracy associated with pathologies such as corruption, collusion, nepotism (KKN), slow service performance, and an inability to meet public satisfaction. Digital leadership among heads of local government agencies is expected to contribute significantly to achieving bureaucratic reform. This study aims to analyze the role of digital leadership in facilitating bureaucratic reform in South Sulawesi Province and to formulate a digital leadership model for effective bureaucratic reform. The research employs digital leadership theory as outlined by Klein (2020), which encompasses business characteristics, attitudinal characteristics, and general characteristics, serving as the analytical framework to assess the state of digital leadership among local government leaders in South Sulawesi. The study adopts a qualitative descriptive method, with primary data collected through observations and interviews with key informants. Data analysis techniques include data reduction, data display, and drawing conclusions. The findings conclude that: 1) Not all local government leaders possess effective digital leadership skills, which results in suboptimal contributions to bureaucratic reform. This is evident through the evaluation of business characteristics, attitudinal characteristics, and general characteristics that have yet to support reform in institutional structuring, administrative processes, human resource management, and service delivery. 2) The researcher formulated the “S4P Digital Leadership Model,” developed from Klein’s (2020) digital leadership model, which is believed to contribute to more effective bureaucratic reform. The novelty of this model lies in the incorporation of local wisdom dimensions—Sipakatau, Sipakalebbi, Sipakinge, and Sirri na Pacce—as well as digital leadership prerequisites such as digital literacy, innovation, and collaboration. This comprehensive, contextually relevant, and responsive model can be implemented across different regions in Indonesia, utilizing local cultural values as guiding principles for governance and public service delivery.